Analisis Perilaku Kepatuhan Pajak Merchant-Merchant yang Ada di Tokopedia - Ita Andryani; Ning Rahayu (Universitas Medan Area, 2021)
This research was carried out to research the tax compiance behavior of merchants in Tokopedia. This research was analyzed using Structural Equation Modeling (SEM) with the LISREL program. The data used in this research were collected by using questionnaire with a sample of 100 merchants in Tokopedia. Variables in this study include attitudes toward tax compliance, subjective norms, perceived behavioral control, intentions, and tax compliance of merchants in Tokopedia.The results showed that (1) there was a mutually influential relationship between attitudes to comply with subjective norms. (2) there is no mutually influential relationship between subjective norms and perceived behavioral control. (3) there is no mutually influential relationship between attitudes of obedient behavior with perceived behavioral control. (4) there is an influence between the attitude of behaving obediently to the intention of tax compliance. (5) there is no influence between subjective norms on the intention of tax compliance. (6) there is no influence between perceived behavioral control on tax compliance intentions. (7) there is an influence between the perception of behavioral control on tax compliance behavior. (8) there is an influence between the intention to behave obediently to tax compliance.